2020
DOI: 10.3390/ijms21124551
|View full text |Cite
|
Sign up to set email alerts
|

On the Catalytic Activity of the Engineered Coiled-Coil Heptamer Mimicking the Hydrolase Enzymes: Insights from a Computational Study

Abstract: Recently major advances were gained on the designed proteins aimed to generate biomolecular mimics of proteases. Although such enzyme-like catalysts must still suffer refinements for improving the catalytic activity, at the moment, they represent a good example of artificial enzymes to be tested in different fields. Herein, a de novo designed homo-heptameric peptide assembly (CC-Hept) where the esterase activity towards p-nitro-phenylacetate was obtained for introduction of the catalytic triad (Cys-His-Glu) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
(80 reference statements)
2
6
0
Order By: Relevance
“…At the end of the activation step, the EI' structure, is characterized by a CysS − /HisH + zwitterionic pair. Irrespective of an HIE or HID form, our calculations for ES therefore support the finding that Cys145 of the M pro of SARS-CoV-2 works in the neutral form and represents the resting state of the enzyme as previously noted in similar systems [71,80].…”
Section: Inhibition Promoted By Ebssupporting
confidence: 87%
“…At the end of the activation step, the EI' structure, is characterized by a CysS − /HisH + zwitterionic pair. Irrespective of an HIE or HID form, our calculations for ES therefore support the finding that Cys145 of the M pro of SARS-CoV-2 works in the neutral form and represents the resting state of the enzyme as previously noted in similar systems [71,80].…”
Section: Inhibition Promoted By Ebssupporting
confidence: 87%
“…The four most populated structures were used as a starting point for the docking procedure. The described procedure has been successfully adopted in a number of investigations on different enzymes. …”
Section: Methodsmentioning
confidence: 85%
“…It was suggested that during the reaction, a shrinking of this distance may occur, leading O3′ to become closer to Pα and consequently facilitating the nucleophilic attack. The little longer distance in ddhCTP than that in CTP could affect the O3′–P α alignment for catalysis during the nucleophilic attack, in the reactive Michaelis–Menten complex. …”
Section: Results and Discussionmentioning
confidence: 99%
“…The General Amber Force Field (GAFF) and the Restrained Electrostatic Potential method were adopted to extrapolate non-bonding parameters and charges, respectively [ 26 , 27 ]. The here-adopted parametrization procedure represents a well-assessed protocol that was successfully adopted in previous studies [ 28 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%